2015
DOI: 10.1371/journal.pone.0119757
|View full text |Cite
|
Sign up to set email alerts
|

Absolute vs. Weight-Related Maximum Oxygen Uptake in Firefighters: Fitness Evaluation with and without Protective Clothing and Self-Contained Breathing Apparatus among Age Group

Abstract: During fire emergencies, firefighters wear personal protective devices (PC) and a self-contained breathing apparatus (S.C.B.A.) to be protected from injuries. The purpose of this study was to investigate the differences of aerobic level in 197 firefighters (age: 34±7 yr; BMI: 24.4±2.3 kg.m-2), evaluated by a Queen’s College Step field Test (QCST), performed with and without fire protective garments, and to analyze the differences among age groups (<25 yr; 26-30 yr, 31-35 yr, 36-40 yr and >40 yr). Variance anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 40 publications
(49 reference statements)
3
16
3
Order By: Relevance
“…In the multivariable model incorporating the individual compounding factors, body weight and resting heart rate are independently associated with the estimated VO 2 max. These findings are consistent with previous studies those examined the influence of body weight [ 57 , 75 ] and resting heart rate [ 76 , 77 ] on VO 2max .…”
Section: Discussionsupporting
confidence: 93%
“…In the multivariable model incorporating the individual compounding factors, body weight and resting heart rate are independently associated with the estimated VO 2 max. These findings are consistent with previous studies those examined the influence of body weight [ 57 , 75 ] and resting heart rate [ 76 , 77 ] on VO 2max .…”
Section: Discussionsupporting
confidence: 93%
“…Ryan et al [72] found that lower limb strength, specifically at fast velocities, was critical for work performance in jobs that were physically demanding. In this study, CMJ values of male were higher than those previously reported by studies of Perroni and colleagues [14,53] for the same age Italian firefighter recruits. Considering that the results of CMJ in the female group in this study showed lower value than male at all different age previously analyzed [14,53], we agree with Rhea et al [11] that there is a need to include muscle strength and muscle endurance in fitness training of firefighters.…”
Section: Plos Onecontrasting
confidence: 70%
“…kg -1. min -1 ,respectively). In other studies of the same group [4,53], a high correlation between absolute VO 2max values and tests performed with and without PC & SCBA, by firefighters' recruits, had been found. They suggested that VO 2max assessed in absolute value could facilitate a comparison between the same firefighters and different subjects during a specific period of physical conditioning.…”
Section: Plos Onementioning
confidence: 67%
“…Normalisation of aerobic capacity to body mass, in part for ease of comparison between personnel of different body sizes, is prevalent in professions that involve load carriage 19,27,28 .…”
Section: Aerobic Capacity and Body Massmentioning
confidence: 99%
“…For individuals with higher body mass, a given load will represent a smaller percentage of body mass than for lighter counterparts, whichusually results in a lower relative metabolic demand to perform the same task.This relationship can become less clear in thetranslationto exercise tolerancebetween unloaded and heavily-loaded conditions, where the negative correlation between body mass and reduction in exercise time is only smallto-moderate 18 .As such, examining body composition rather than solely body mass may be prudent in physically demanding occupations. Although it is customary in health research to use VO 2 max normalised to body size, for occupations that involve external load carriage absolute units may be more suitable 8,19 .…”
Section: Introductionmentioning
confidence: 99%